Genetic architecture of human plasma lipidome and its link to cardiovascular disease - Rubina Tabassum (Nature Portfolio, 2019)
Cardiovascular diseases (CVD) are associated with plasma lipid levels. Here, Tabassum et al. perform genome-wide association studies for lipidomic profiles with 141 (non-standard) lipid species which highlights shared genetic loci with CVD and that traditional lipids have low genetic correlation with other lipids.